2015
DOI: 10.1371/journal.pmed.1001833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Therapy on Cognition and Mood in Recently Postmenopausal Women: Findings from the Randomized, Controlled KEEPS–Cognitive and Affective Study

Abstract: BackgroundMenopausal hormone therapy (MHT) reportedly increases the risk of cognitive decline in women over age 65 y. It is unknown whether similar risks exist for recently postmenopausal women, and whether MHT affects mood in younger women. The ancillary Cognitive and Affective Study (KEEPS-Cog) of the Kronos Early Estrogen Prevention Study (KEEPS) examined the effects of up to 4 y of MHT on cognition and mood in recently postmenopausal women.Methods and FindingsKEEPS, a randomized, double-blinded, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
238
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 365 publications
(274 citation statements)
references
References 71 publications
11
238
2
10
Order By: Relevance
“…Also, a beneficial effect of norethisterone in combination with estradiol has been found in randomized clinical trial in healthy as well as in sAD postmenopausal women [95,96]. The KEEPS study used treatment with two types of estrogen (CEE orally and 17β-estradiol in a transdermal patch with or without micronized progesterone (MP)) and did not find any beneficial effects on cognition [13] (Table 4). However, in a group of ApoE ε4 carriers treated with low concentrations of estradiol (50µg), lower levels of Aβ deposit were found in comparison to non-carriers [97].…”
Section: Type (Composition) Of Htmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, a beneficial effect of norethisterone in combination with estradiol has been found in randomized clinical trial in healthy as well as in sAD postmenopausal women [95,96]. The KEEPS study used treatment with two types of estrogen (CEE orally and 17β-estradiol in a transdermal patch with or without micronized progesterone (MP)) and did not find any beneficial effects on cognition [13] (Table 4). However, in a group of ApoE ε4 carriers treated with low concentrations of estradiol (50µg), lower levels of Aβ deposit were found in comparison to non-carriers [97].…”
Section: Type (Composition) Of Htmentioning
confidence: 99%
“…On one hand there is WHIMS, and the Women's Health Initiative Memory Study of cognitive aging (WHIMSCA) reporting a negative effect of HT on cognition. [11,15,16] On the other hand, the Women's Health Initiative Memory Study/young (WHIMS-Y) and KEEPS-Cog showed no beneficial effectn cognition (Table 4) [13,106] .…”
Section: Randomised Interventional Clinical Trials In Women With Unimmentioning
confidence: 99%
See 3 more Smart Citations